The bystander cell-killing effect mediated by nitric oxide in normal human fibroblasts varies with irradiation dose but not with radiation quality. (May 2015) - Yokota, Yuichiro; Funayama, Tomoo; Mutou-Yoshihara, Yasuko; Ikeda, Hiroko; Kobayashi, Yasuhiko
Abstract Purpose: To investigate the dependence of the bystander cell-killing effect on radiation dose and quality, and to elucidate related molecular mechanisms. Materials and methods: Normal human fibroblast WI-38 cells were irradiated with 0.125 - 2 Gy of γ-rays or carbon ions and were co-cultured with non-irradiated cells. Survival rates of bystander cells were investigated using the colony formation assays, and nitrite concentrations in the medium were measured using the modified Saltzman method. Results: Survival rates of bystander cells decreased with doses of γ-rays and carbon ions of ≤ 0.5 Gy. Treatment of the specific nitric oxide (NO) radical scavenger prevented reductions in survival rates of bystander cells. Moreover, nitrite concentrations increased with doses of less than 0.25 Gy (γ-rays) and 1 Gy (carbon ions). The dose responses of increased nitrite concentrations as well as survival reduction were similar between γ-rays and carbon ions. In addition, negative relationships were observed between survival rates and nitrite concentrations. Conclusion: The bystander cell-killing effect mediated by NO radicals in normal human fibroblasts depends on irradiation doses of up to 0.5 Gy, but not on radiation quality. NO radical production appears to be an important determinant of γ-ray- and carbon-ion-induced bystander effects.